Synthesis and characterization of hydroxyapatite nanoparticles and their effects on remineralization of demineralized enamel in the presence of Er,Cr: YSGG laser irradiation - Fatemeh Maddah; Mehdi Shirinzad; Zahra Khalafi; Loghman Rezaei-Soufi; Younes Mohammadi; Fatemeh Eskandarloo; Abbas Farmany (BMC, 2023)
Abstract Background This study aims to synthesize and characterize hydroxyapatite nanoparticles (nano-HA) and evaluate their effects on the remineralization of demineralized enamel in the presence to Er,CR: YSGG laser irradiation. Materials and methods Enamel specimens from 44 human molars were divided into four groups: control, demineralized enamel, demineralized enamel treated with nano-HA, and demineralized enamel treated with nano-HA followed by Er,Cr:YSGG laser irradiation (0.5, 20 Hz, 60 µs, 20 s). Vickers microhardness test was used to evaluate the enamel surface hardness. The morphology and chemistry of enamel surfaces were assessed using scanning electron microscopy (SEM) and Raman spectroscopy, respectively. Result The result of this study showed that the application of Er,CR: YSGG laser irradiation to demineralized enamel treated with nano-HA had the highest impact on its microhardness. Conclusion ER,CR: YSGG laser irradiation promotes enamel remineralization after treatment with nano HA.